First record of the zoophytophagous plant bug Atractotomus mali (Hemiptera: Miridae) in Quebec orchards - Saguez, Julien; Lasnier, Jacques; Schwartz, Michael; Vincent, Charles (Phytoprotection, 2015)
Atractotomus mali (Meyer-Dür, 1843) (Hemiptera: Miridae) is a zoophytophagous insect associated with orchards in Europe and North America. In Canada, it has previously been reported in apple (Malus domestica Borkh) orchards in several provinces, but mainly in Nova Scotia, where it induced more damage on fruit than predatory effects. During the summer of 2014, we collected 33 specimens in an apple orchard in Magog (QC, Canada), using a tapping method. This study constitutes the first record of A. mali in Quebec.